Rate-regulated power control for supporting flexible transmission in future CDMA mobile networks. - Dongwoo Kim
In code division multiple access (CDMA) mobile networks, transmitted power is controlled to provide each user an acceptable connection by limiting the interference seen by other users. Previous work has focused on finding a power assignment that maximizes the minimum carrier-to-interference ratio where the transmission rate of each user is known and fixed. In future mobile networks, however, fluctuations in mobiles' transmission rate should be considered in designing power control algorithms. In this work, we present an algorithm for controlling mobiles' transmitter power levels while explicitly handling their time-varying transmission rates. During the whole power control process, the required signal quality is always maintained. The traffic-carrying performance of the algorithm is evaluated by simulation where different types of users are sending burst data
Keywords: CDMA mobile networks; RFI; Burst data transmission; Code division multiple access; Flexible transmission; Minimum carrier-to-interference ratio; Power control algorithms; Rate-regulated power control; Signal quality; Simulation; Time-varying transmission rates; Traffic-carrying performance; Transmission rate; Transmitted power